A radical form of nitric oxide inhibits porcine circovirus type 2 replication in vitro - Tao Xue; Jizong Li; Chuanmin Liu (BMC Veterinary Research, 2019)
Abstract Background Porcine circovirus type 2 (PCV2) is the causal agent of postweaning multisystemic wasting syndrome (PMWS), causing large economical losses of the global swine industry. Nitric oxide (NO), as an important signaling molecule, has antiviral activity on some viruses. To date, there is little information on the role of NO during PCV2 infection. Results We used indirect fluorescence assay (IFA), TCID50, real-time RT-qPCR and western blot assay to reveal the role of NO in restricting PCV2 replication. PCV2 replication was inhibited by a form of NO, NO • , whereas PCV2 was not susceptible to another form of NO, NO+. Conclusion Our findings indicate that the form of NO • has a potential role in the fight against PCV2 infection.